Redox-active tyrosine residue in the microcin J25 molecule - Chalon, Miriam Carolina (2011)
Microcin J25 (MccJ25) is a 21 amino acid lasso-peptide antibiotic produced by Escherichia coli and composed of an 8-residues ring and a terminal 'tail' passing through the ring. We have previously reported two cellular targets for this antibiotic bacterial RNA polymerase and the membrane respiratory chain, and shown that Tyr9 is essential for the effect on the membrane respiratory chain which leads behavior of MccJ25 and the mutant MccJ25 (Y9F). Cyclic voltammetry measurements showed irreversible oxidation of both Tyr9 and Tyr20 in MccJ25, but infrared spectroscopy studies demonstrated that only Tyr9 could be deprotonated upon chemical oxidation in solution. Formation of a long-lived tyrosyl radical in the native MccJ25 oxidized by H2O2 was demonstrated by Electron Paramagnetic Resonance Spectroscopy; this radical was not detected when the reaction was carried out with the MccJ25 (Y9F) mutant. These results show that the essential Tyr9, but not Tyr20, can be easily oxidized and form a tyrosyl radical.